2017
DOI: 10.2147/cia.s144795
|View full text |Cite
|
Sign up to set email alerts
|

The link between weight shift asymmetry and gait disturbances in chronic hemiparetic stroke patients

Abstract: IntroductionWhile the asymmetry of body posture and the asymmetrical nature of hemiparetic gait in poststroke (PS) patients are well documented, the role of weight shift asymmetry in gait disorders after stroke remains unclear.ObjectiveWe examined the association of weight-bearing asymmetry (WBA) between paretic and nonparetic lower limbs during quiet standing with the degree of deviation of hemiplegic gait from normal gait evaluated by the Gillette Gait Index (GGI) incorporating 16 distinct clinically importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
1
15
0
7
Order By: Relevance
“…Previous studies have described a frequent nonefficient neuromuscular control of trunk stability and inaccurate trunk muscle recruitment patterns of control of the spinal load in relation to a given task and posture in these patients 3–5 . This is also associated with symptoms such as asymmetric posture, abnormal body imbalance, and deficit of weight transfer 6 …”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have described a frequent nonefficient neuromuscular control of trunk stability and inaccurate trunk muscle recruitment patterns of control of the spinal load in relation to a given task and posture in these patients 3–5 . This is also associated with symptoms such as asymmetric posture, abnormal body imbalance, and deficit of weight transfer 6 …”
Section: Introductionmentioning
confidence: 94%
“…Chengetanai et al in their study observed that as the asymmetry in weight distribution increases between the limbs, there was a decrease in scores of BBS with movement activities. This was attributed to an inability of the patients to transfer weight (weight shifts) onto either the limb which is very essential for smooth and efficient execution of activities of daily living involving balance and movement [18,30].…”
Section: Discussionmentioning
confidence: 99%
“…They observed a significant negative association between weight-bearing asymmetry, paretic step length, and walking speed. The probable explanation for these findings could be kinematic deviations in gait such as asymmetrical movement of the pelvis, inadequate paretic hip and knee flexion in swing phase, and excessive ankle plantar flexion that affect the spatiotemporal parameters [30]. Furthermore, Adegoke et al in a study evaluating asymmetry of weight bearing on the lower limbs and the association between PWBA and functional ambulation performance in ambulant stroke survivors found a strong correlation between the outcomes [18].…”
Section: Discussionmentioning
confidence: 99%
“…with dynamometers, pressure sensitive walkways or body worn accelerometers), allowing the disentanglement of the exact components responsible for mobility limitation. In contrast to most functional tests, these measures can also account for the asymmetry, which is typical for stroke patients [ 23 , 24 ]. Rehabilitative measures to restore LEPF in people after stroke include physical therapy, exercise (including training of balance, strength and gait), and the provision of adaptive devices [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%